Penerapan Building Information Modeling (BIM) untuk Pengestimasian Biaya Proyek Pembangunan Pos Jaga di SD dan SMP Terpadu Balikpapan Selatan - Tama, Wira Adi; Permata, Iza Putra; Hendriyani, Irna; Pratiwi, Reno (Jurnal Talenta Sipil, 2024)
With the development of the AEC (Architecture, Engineering and Construction) industry, currently a lot of software has been developed to meet the needs of the construction industry with the aim of minimizing human error due to conventional data processing. This study aims to analyze the results of volume and cost comparisons using the 5D Building Information Modeling (BIM) concept with conventional methods in the New School Unit construction project for integrated Elemntary School and Junior High School development in the South Balikpapan sub-district. By using Revit, the 2D image obtained from the consultant is modeled back into 3D form so that the material volume requirements become more detailed. It can be seen from the consultant's calculation of 961.46kg from the Autodeks Revit 621.34kg software that there is a difference of 340.12kg or 35%, for the volume of concrete work from The consultant's calculation has a volume of 17.65m3 from the Autodeks Revit software which has a volume of 12.01m3, a difference of 5.64m3 or 32%. For concrete work costs from consultants amounting to Rp14,787,292.87 from Autodeks Revit software Rp9,549,377.76, which has a difference of Rp5,237,915.11 or 35%, for concrete work costs from consultants amounting to Rp19,373,381 from Autodeks Revit software, the cost is Rp13,078,977, which has a difference of Rp6,294,404.07 or 32%. This illustrates that using the 3D BIM concept supported by Revit software is able to provide detailed material take-off results so as to reduce wasted material and support the 5D BIM concept in supporting cost estimation calculations.